2008
DOI: 10.1080/01443610701811837
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early voiding dysfunction after tension-free vaginal tape

Abstract: The purpose of this study was to determine whether early postoperative voiding dysfunction can be predicted before inserting a tension-free vaginal tape (TVT). Multiple parameters including demographic data, history of previous anti-incontinence surgery, anaesthetic type, operator experience, type of surgical procedure (TVT alone or combined with other prolapse surgery) and preoperative urodynamic studies were analysed by univariate analysis and stepwise multiple logistic regression. The data from 500 women we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Their study showed a strong association between VD and concomitant prolapse surgery. Duckett et al [14] performed a retrospective study on 500 TVT patients. They found VD in 5.8 %, which concurred with our results of 4 %.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed a strong association between VD and concomitant prolapse surgery. Duckett et al [14] performed a retrospective study on 500 TVT patients. They found VD in 5.8 %, which concurred with our results of 4 %.…”
Section: Discussionmentioning
confidence: 99%
“…The studies with the focus on surgical management of voiding dysfunction determined a proportion of surgical intervention because of urinary retention from 1.7 to 11% (table 3). Various factors were shown to be associated with postoperative voiding difficulties, including the age of the patient [20,21,22], abnormal preoperative uroflow pattern [20,21,23,24], general anesthesia [23], previous incontinence surgery [21], an inexperienced surgeon [8], recurrent surgery [19], concurrent vault suspension surgery [7], and postoperative urinary tract infection [7]. Other authors do not corroborate these risk factors [10,25].…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have evaluated the effect of anesthesia in the placement of midurethral slings, none has directly compared GA with MAC [12][13][14][15]. One randomized controlled trial of women undergoing minislings with Gynecare TVT-Secur TM compared local anesthesia with intravenous sedation (lidocaine with midazolam/fentanyl) with GA and found a higher level of pain 1 h postoperatively and longer recovery time in the GA group [12].…”
Section: Discussionmentioning
confidence: 99%